Bioenergetic and proteolytic defects in fibroblasts from patients with sporadic Parkinson's disease (2014)
Background: Parkinson's disease (PD) is a complex disease and the current interest and focus of scientific research is both investigating the variety of causes that underlie PD pathogenesis, and identifying reliable biomarkers to diagnose and monitor the progression of pathology. Investigation on pathogenic mechanisms in peripheral cells, such as fibroblasts derived from patients with sporadic PD and age/gender matched controls, might generate deeper understanding of the deficits affecting dopaminergic neurons and, possibly, new tools applicable to clinical practice. Methods: Primary fibroblast cultures were established from skin biopsies. Increased susceptibility to the PD-related toxin rotenone was determined with apoptosis- and necrosis-specific cell death assays. Protein quality control was evaluated assessing the efficiency of the Ubiquitin Proteasome System (UPS) and protein levels of autophagic markers. Changes in cellular bioenergetics were monitored by measuring oxygen consumption and glycolysis-dependent medium acidification. The oxido-reductive status was determined by detecting mitochondrial superoxide production and oxidation levels in proteins and lipids. Results: PD fibroblasts showed higher vulnerability to necrotic cell death induced by complex I inhibitor rotenone, reduced UPS function and decreased maximal and rotenone-sensitive mitochondrial respiration. No changes in autophagy and redox markers were detected. Conclusions: Our study shows that increased susceptibility to rotenone and the presence of proteolytic and bioenergetic deficits that typically sustain the neurodegenerative process of PD can be detected in fibroblasts from idiopathic PD patients. Fibroblasts might therefore represent a powerful and minimally invasive tool to investigate PD pathogenic mechanisms, which might translate into considerable advances in clinical management of the disease. © 2014 Elsevier B.V.